Geographical distribution of Austrolebias monstrosus (Huber 1995), A. elongatus (Steindachner 1881) and A. vandenbergi(Huber 1995) (Teleostei: Cyprinodontiformes), with comments on the biogeography and ecology of Rivulidae in Pampasic and Chaco floodplains - Alonso, Felipe (2016)
After several collecting trips in Argentina and a revision of material deposited in national ichthyological collections we present a new record for Austrolebias elongatus from Gualeguaychú, in Entre Ríos Province, Argentina. Also, we present evidence on the erroneous record of Austrolebias monstrosus, and A. vandenbergi from Ituzaingó, Corrientes Province. Additional records from Salta Province are presented for those species. Material determined as A. elongatus from Santiago del Estero is also attributed to A. monstrosus. Therefore we restrict the distribution of these two species to Semi-arid Chaco Region in Argentina, Paraguay and Bolivia.